CONSTRAINTS AND ROLE OF AGRICULTURAL EXTENSION PARTNERSHIPS IN APPLICATION RICE FIELD RICE CULTIVATION INNOVATIONS TO REALIZE FOOD SECURITY - Setia Budi; Eva Wardah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Research in the long term aims to produce a partnership model in the application of lowland rice cultivation innovations to increase rice production to realize food security in the region in Aceh Province. In particular, this study aims to (1) identify and analyze the constraints in increasing rice production in Pidie Jaya Regency, (2) identify and analyze the role of agricultural extension partners in implementing innovations in lowland rice cultivation in Pidie Jaya Regency. This research is an action research on the application of innovation combined with a survey method which was carried out to see the pattern of partnerships in the application of innovation in lowland rice cultivation to realize food security in Pidie Jaya Regency. The location of this research was conducted intentionally in Pidie Jaya Regency. Focus Group Discussion) with stakeholders aboutthe potential role of each party in the partnership pattern. The results of the study showinnovations applied to lowland rice cultivation for food security include; superior seed innovation, land management, cropping system with agricultural mechanization, jajar legowo planting pattern, biological pest control (Rubuha), balanced fertilization and harvest implementation using agricultural mechanization. (1) constraint indicatorsthe availability of fertilizers (very constrained), pest and disease attacks, and the availability of extension workers, and the availability of agricultural tools and machinery (constrained) as well as garden patterns that are not simultaneously, the availability of irrigation water, and the low use of superior seeds are in the less constrained category. (2) farmers perceive the role of partners in implementing innovations in rice field cultivationlocal governments and farmers' institutions have played a role, while universities and the private sector/entrepreneurs are in the category of having quite a role.